(untitled) (Nigerian Journal of Technology, 2018)
The objective of the study is to replace coarse natural aggregate with recycled concrete coarse aggregate (RCCA) for concrete production in order to determine the compressive strength of such concrete for different percentages of partial replacement using different water/cement ratios. Thereafter develop a predictive model for the compressive strength using different percentages of partial replacement and water/cement ratios. The polynomial regression model was applied to examine the correlation between the compressive strength of concrete, water cement ratio and %RCCA. The following regression models were established for 28 days at 0.4, 0.45 and 0.50 water cement ratio, = - - 0.192(%) + 49.79 with R² = 1, = 0.000(%)2 - 0.371(%) + 44.29 with R² = 1, and = -0.001(%RCCA)2 - 0.386(%) + 41.91 with R² = 1. At 28days test for water cement ratios of 0.55, 0.6 and 0.65 as = -0.0001(%)2 - 0.158(%) + 38.26 with coefficient of determination of R² = 1, = 0.010(%)2 - 0.1954 (%) + 28.29 with R² = 1, while for W/C ratio of 0.65 is given as = -0.001(%)2 + 0.222(%) + 18.37 with coefficient of determination, R² = 1. It was concluded that the increase or decrease in compressive strength of concrete was dependent on percentage replacement ratio of natural aggregate to recycled concrete aggregate (%RCCA) and the amount of water to cement ratio (w/c) ratio of the mix. The significance of the study is that the compressive strength of concrete made with RCCA which is a waste product can be predicted by using the predictive model developed. http://dx.doi.org/10.4314/njt.v37i3.11